2021
DOI: 10.33830/jelajah.v3i1.1847
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Tourist Satisfaction and Revisit Intention to Cibuntu Tourist Village During Covid-19 Pandemic

Abstract: The COVID-19 pandemic has a devastating impact on all world economic activities, including the tourism industry. Tourist satisfaction and revisit intention are two important factors in the recovery of economic activity in the tourism sector. These two variables are also influenced by tourists' perceptions of the COVID-19 protocol implemented by tourist destinations. Desa Wisata Cibuntu puts forward the concept of community-based tourism. Located in Kuningan Regency, West Java, its’ homestay is their main busin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 0 publications
1
5
0
3
Order By: Relevance
“…Figure 3 below presents the geographical contexts where empirical studies were conducted. We found that most of the empirical research was carried out in Indonesia (n 5 12) (Afriani and Sugiarto, 2020;Alwi et al, 2022;Azis et al, 2020;Bustan and Setiawan, 2021;Kadir et al, 2020;Lemy et al, 2020;Pinem et al, 2021;Sianipar et al, 2021;Sihotang and Sukaatmadja, 2021;Sitinjak et al, 2021;Sukaatmadja et al, 2022;Zainuddin et al, 2022). After that, 7 studies were based on the data collected from China (Agyeiwaah et al, 2021;Cai et al, 2021a;Han et al, 2021;Hu and Xu, 2021;Jiang et al, 2022;Riestyaningrum et al, 2020;Zeng and Li, 2021) followed by the Malaysia (n 5 5) (Ahmad et al, 2021a, b;Hanafiah et al, 2021;Ramli et al, 2021;Tiam Chin et al, 2021) and India (n 5 4) (Gupta et al, 2021;Kour et al, 2021;Rather, 2021a, b) and in Korea (n 5 4) (Shin et al, 2022;Sinha and Nair, 2021;Yoo et al, 2022;Yu et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 3 below presents the geographical contexts where empirical studies were conducted. We found that most of the empirical research was carried out in Indonesia (n 5 12) (Afriani and Sugiarto, 2020;Alwi et al, 2022;Azis et al, 2020;Bustan and Setiawan, 2021;Kadir et al, 2020;Lemy et al, 2020;Pinem et al, 2021;Sianipar et al, 2021;Sihotang and Sukaatmadja, 2021;Sitinjak et al, 2021;Sukaatmadja et al, 2022;Zainuddin et al, 2022). After that, 7 studies were based on the data collected from China (Agyeiwaah et al, 2021;Cai et al, 2021a;Han et al, 2021;Hu and Xu, 2021;Jiang et al, 2022;Riestyaningrum et al, 2020;Zeng and Li, 2021) followed by the Malaysia (n 5 5) (Ahmad et al, 2021a, b;Hanafiah et al, 2021;Ramli et al, 2021;Tiam Chin et al, 2021) and India (n 5 4) (Gupta et al, 2021;Kour et al, 2021;Rather, 2021a, b) and in Korea (n 5 4) (Shin et al, 2022;Sinha and Nair, 2021;Yoo et al, 2022;Yu et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, destination-related factors are those factors that enhance tourists to visit or revisit the destination in this pandemic situation. For example, general sale promotion, perceived trust, tourist attraction, service quality, demographic characteristics, destination image, destination attachment, attractiveness, accommodation on service, airport service quality, innovative measures, staff-and traveler-related measures, sanitization and logistics operations positive perception or impressions of a destination is likely to mold the decision in destination's favor to revisit destination(Cifci, 2021;Hassan and Soliman, 2021;Kadir et al, 2020;Kour et al, 2021;Pinem et al, 2021;Ramli et al, 2021;Sianipar et al, 2021;Sihotang and Sukaatmadja, 2021).…”
mentioning
confidence: 99%
“…Therefore, tourist village should be developed along with attractions that follow the development of the tourism model [51]. Tourists' satisfaction and intention to revisit the tourist village are also important components to the sustainability of tourism activities [52]. The strategies that can be taken in the development of Embung Setumpeng tourist object post-Covid-19 pandemic are to improve and to construct new facilities in the Embung Setumpeng tourist object area.…”
Section: Improving Facilities Of Embung Setumpeng Tourist Objectmentioning
confidence: 99%
“…Pariwisata telah menjadi pendorong penting dalam pengembangan ekonomi lokal, pelestarian budaya, dan pemberdayaan masyarakat di berbagai wilayah (Ismanto et al, 2023). Fenomena ini semakin menonjol di Indonesia, terutama dengan berkembangnya tren wisata perdesaan atau desa wisata, yang menarik minat baik dari wisatawan domestik maupun internasional (Sianipar et al, 2021). Desa Wisata Besani, yang terletak di Kabupaten Batang, Provinsi Jawa Tengah, adalah contoh nyata dari destinasi pariwisata yang menarik, karena menggabungkan harmonisasi antara tradisi budaya Jawa dan pengaruh Tionghoa yang kaya (Yulius, 2023).…”
unclassified
“…Salah satu daya tarik utama dari Desa Wisata adalah pondok wisata, yang menawarkan penginapan yang lebih intim dan dekat dengan masyarakat setempat, memberikan pengalaman yang berbeda dan memuaskan bagi para wisatawan yang mencari keautentikan dan kebersamaan dalam perjalanan mereka (Sianipar et al, 2021;Sudarmayasa et al, 2020;Wiguna et al, 2018). Oleh karena itu, penting untuk memahami peran penting pondok wisata dalam konteks pariwisata perdesaan yang berkelanjutan (Janjua et al, 2021;Li et al, 2024).…”
unclassified